Ten years of strong opioid analgesics consumption in Malaysia and other Southeast Asian countries - Zin, Che Suraya (2019)
Abstract Background: It was reported that opioid consumption in developing countries was stagnated or decreased but precise data on the consumption are unclear. This study examined the trends and patterns of opioid consumption in Malaysia and other four Southeast Asian countries.